Cellular and Molecular Gradients in the Ventral Horns With Increasing Distance From the Injury Site After Spinal Cord Contusion - Kabdesh, Ilyas M.; Mukhamedshina, Yana O.; Arkhipova, Svetlana S.; Sabirov, Davran K.; Kuznecov, Maxim S.; Vyshtakalyuk, Alexandra B.; Rizvanov, Albert A.; James, Victoria; Chelyshev, Yuri A. (Frontiers in Cellular Neuroscience, 2022)
To identify cellular and molecular gradients following spinal cord injury (SCI), rat contusion model of severe SCI was used to investigate the expression of NG2 and molecules that identify astrocytes and axons of the ventral horns (VH) at different distances on 7 and 30 days post injury (dpi). A gradient of expression of NG2+/Olig2+ cells was determined, with the highest concentrations focused close to the injury site. A decrease in NG2 mean intensity correlates with a decrease in the number of NG2+ cells more distally. Immunoelectron microscopy subsequently revealed the presence of NG2 in connection with the membrane and within the cytoplasm of NG2+ glial cells and in large amounts within myelin membranes. Analysis of the astrocyte marker GFAP showed increased expression local to injury site from 7 dpi, this increase in expression spread more distally from the injury site by 30 dpi. Paradoxically, astrocyte perisynaptic processes marker GLT-1 was only increased in expression in areas remote from the epicenter, which was traced both at 7 and 30 dpi. Confocal microscopy showed significant decrease in the number of 5-HT+ axons at distance from the epicenter in caudal direction, which is consistent with a decrease in β3-tubulin in these areas. The results indicate significant cellular and molecular reactions not only in the area of the gray matter damage, but also in adjacent and remote areas, which is important for assessing the possibility of long-distance axonal growth.